Work‐Function Engineering in Lead Sulfide and Cadmium Sulfide Quantum Dots incorporated into Zeolite Y using Ion Exchange. (2nd February 2016) - Lee, Hangil; Kim, Hyun Sung
Abstract : The work function is a key property that should be considered to enhance the performance of quantum‐dot (QD) applications. Here, the ability to effectively control the work‐function value of zeolite‐encapsulated PbS and CdS QDs by choosing the type of cation in the framework is reported. This study will provide new insight for developing applications of the QD‐zeolite composites.